Responses of Lucilia sericata (Diptera: Calliphoridae) to compounds from microbial decomposition of larval resources. (May 2016) - Liu, Wenqi; Longnecker, Michael; Tarone, Aaron M.; Tomberlin, Jeffery K.
Abstract : Decomposition of vertebrate carrion is partially due to microbes, which release a series of volatile organic compounds (VOCs) at various concentrations. These VOCs are part of ecologically relevant public information that serve as cues attracting blow flies (Diptera: Calliphoridae), such as Lucilia sericata, to remains as a resource both for themselves and for their offspring. However, these responses are partially governed by sex and physiological state (e.g. gravid and nongravid) of the fly and concentration of the VOCs. We examined the responses of 7–9-day-old L. sericata adults to dimethyldisulphide, indole, isobutylamine and phenylacetic acid in a Y-tube olfactometer. These VOCs are associated with vertebrate decomposition, carrion-mimicking flowers as well as fly-attracting bacteria. Our results demonstrate a relationship between sex and physiological state with regard to dose-dependent attraction to VOCs that occur during decomposition, suggesting that specific decomposition molecules provide distinct types of information to the flies with differing foraging interests. Understanding this dynamic relationship provides insight into the mechanisms regulating arthropod colonization, competition and resulting succession in association with such ephemeral resources. Highlights: Blow flies utilize public information from microbes to assess ephemeral resource quality. Flies assessed the availability of essential amino acids in microbial compounds. Flies' responses to microbial compounds were associated with microbial community manipulation. Sex and physiological state of flies influenced dose-specific responses to microbial compounds. Our results indicate a trophic interaction between blow flies and bacteria on ephemeral resources.